It's not bragging if it's true - Avant-garde, Zaila; Dumas, Marti (Random House, 2023)
"Kids will be inspired to embrace their inner weirdness and persevere through obstacles after reading this empowering collection of true stories from teenage Scripps National Spelling Bee champ and Guinness World Record holder Zaila Avant-garde!"--